If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6 = 74whatisx Reorder the terms: -6 + 8x = 74whatisx Solving -6 + 8x = 74ahistwx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-74ahistwx' to each side of the equation. -6 + -74ahistwx + 8x = 74ahistwx + -74ahistwx Combine like terms: 74ahistwx + -74ahistwx = 0 -6 + -74ahistwx + 8x = 0 Add '6' to each side of the equation. -6 + -74ahistwx + 6 + 8x = 0 + 6 Reorder the terms: -6 + 6 + -74ahistwx + 8x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -74ahistwx + 8x = 0 + 6 -74ahistwx + 8x = 0 + 6 Combine like terms: 0 + 6 = 6 -74ahistwx + 8x = 6 Reorder the terms: -6 + -74ahistwx + 8x = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + -74ahistwx + 8x = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-3 + -37ahistwx + 4x) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + -37ahistwx + 4x)' equal to zero and attempt to solve: Simplifying -3 + -37ahistwx + 4x = 0 Solving -3 + -37ahistwx + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -37ahistwx + 3 + 4x = 0 + 3 Reorder the terms: -3 + 3 + -37ahistwx + 4x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -37ahistwx + 4x = 0 + 3 -37ahistwx + 4x = 0 + 3 Combine like terms: 0 + 3 = 3 -37ahistwx + 4x = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -13-21p=8 | | -7r-16=-3r-8r | | 2x-(5-x)-7=x-4x | | 3y-xy=-4x-9 | | 3(x-2)=5x-3 | | 6-4x=7x-9-8 | | 5x^2+25x+30=-5x^2 | | 3x(-12)-6=4x | | 4+1-3m-3m=-2m-3m | | 1.2(7.2-0.3x)=-4.1x | | 4x-3(-2x+5)=40 | | 2x^2+3x-24=0 | | x^2-24x+50=-8x+2 | | x+2x+(x-12)=180 | | -(8y+2)-(7y-5)=-1 | | 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 |